Modeling and assessment of atmospheric delay for GPS/Galileo/BDS PPP-RTK in regional-scale - Yin, X.; Chai, H.; El-Mowafy, Ahmed; Zhang, Y.; Zhang, Y.; Du, Z. (ELSEVIER SCI LTD, 2022)
Combining advantages of precise point positioning (PPP) and real-time kinematic (RTK), PPP-RTK has become a promising technology in the mass-market positioning. When performing PPP-RTK, atmospheric corrections enable the user fast ambiguity resolution as well as centimeter accuracy. However, the legacy method of obtaining atmospheric corrections, i.e., interpolating the atmospheric delay based on nearby reference stations, is not regular in space and needs the reference station coordinate information, thereby limiting real-time professional applications. In this contribution, a low-degree polynomial with regular grid residuals is investigated. Forming between-satellite single-differenced slant ionospheric delay, we theoretically analyze the reference network size. Afterwards, the zenith tropospheric delay and slant ionospheric delay accuracy using zero-, first- and second-degree polynomials in calm atmospheric periods are about (5.6, 4.7 and 4.7) mm and (1.9, 1.3 and 1.3) cm. It is therefore recommended to adopt the first-degree polynomial model in terms of the accuracy and transmission load.